The human alpha7 nicotinic acetylcholine receptor is a host target for the rabies virus glycoprotein - O’Brien, Brittany C. V.; Thao, Shelly; Weber, Lahra; Danielson, Helen L.; Boldt, Agatha D.; Hueffer, Karsten; Weltzin, Maegan M. (Frontiers in Cellular and Infection Microbiology, 2024)
The rabies virus enters the nervous system by interacting with several molecular targets on host cells to modify behavior and trigger receptor-mediated endocytosis of the virion by poorly understood mechanisms. The rabies virus glycoprotein (RVG) interacts with the muscle acetylcholine receptor and the neuronal α4β2 subtype of the nicotinic acetylcholine receptor (nAChR) family by the putative neurotoxin-like motif. Given that the neurotoxin-like motif is highly homologous to the α7 nAChR subtype selective snake toxin α-bungarotoxin (αBTX), other nAChR subtypes are likely involved. The purpose of this study is to determine the activity of the RVG neurotoxin-like motif on nAChR subtypes that are expressed in brain regions involved in rabid animal behavior. nAChRs were expressed in Xenopus laevis oocytes, and two-electrode voltage clamp electrophysiology was used to collect concentration-response data to measure the functional effects. The RVG peptide preferentially and completely inhibits α7 nAChR ACh-induced currents by a competitive antagonist mechanism. Tested heteromeric nAChRs are also inhibited, but to a lesser extent than the α7 subtype. Residues of the RVG peptide with high sequence homology to αBTX and other neurotoxins were substituted with alanine. Altered RVG neurotoxin-like peptides showed that residues phenylalanine 192, arginine 196, and arginine 199 are important determinants of RVG peptide apparent potency on α7 nAChRs, while serine 195 is not. The evaluation of the rabies ectodomain reaffirmed the observations made with the RVG peptide, illustrating a significant inhibitory impact on α7 nAChR with potency in the nanomolar range. In a mammalian cell culture model of neurons, we confirm that the RVG peptide binds preferentially to cells expressing the α7 nAChR. Defining the activity of the RVG peptide on nAChRs expands our understanding of basic mechanisms in host-pathogen interactions that result in neurological disorders.